Atrophic gastritis in Helicobacter pylori‐infected children. Issue 3 (20th March 2022) - Hsieh, Hsuan; Yang, Hsiao‐Bai; Sheu, Bor‐Shyang; Yang, Yao‐Jong
Abstract: Background: Helicobacter pylori infection is the leading cause of peptic ulcer and chronic gastritis and may initiate gastric carcinogenesis following the Correa cascade. Another lineage of metaplasia, spasmolytic peptide‐expressing metaplasia (SPEM) has recently been found to be an alternative precursor to gastric cancer. To date, few reports have investigated gastric precancerous lesions among children with H. pylori infection. This study aimed to evaluate the histopathological pattern of H. pylori atrophic gastritis in children and the extent of precancerous lesions. Materials and Methods: This study enrolled pediatric patients with H. pylori infection from 1998 to 2019. During esophagogastroduodenoscopy examinations, biopsy fragments were collected from the gastric antrum and corpus for rapid urease test, culture, and histology evaluation. The presence and degree of chronic inflammation, activity of gastritis, H. pylori density, atrophy, and intestinal metaplasia (IM) were assessed according to the modified Updated Sydney System. Trefoil factor 2 (TFF2) immunohistochemistry was also performed to assess SPEM in the gastric tissues collected from each case using rabbit anti‐human TFF2 antibodies. Results: A total of 92 children with H. pylori infection and adequate gastric mucosa biopsies were enrolled. Esophagogastroduodenoscopy showed that 39 (42.4%) had duodenal ulcers, 11 (12.0%) had gastric ulcers, 41 (44.6%) had gastritis, and 1 (1.1%) had negative findings. Mild‐to‐moderate IM was identified in 4 patients (4.3%). SPEM was found in 8 patients (8.7%) with a significantly higher incidence among female patients (15.8% vs. 8.7%, p  = .031). Gastric glandular atrophy presented in 28 patients (30.4%), and high‐grade atrophy was more common in female patients (3.2% vs. 1.9%, p =  .031). Conclusions: The prevalence rates of atrophic gastritis in the children with H. pylori infection were 30.4% for gastric glandular atrophy, 4.3% for IM and 8.7% for SPEM. SPEM and high‐grade atrophy were more common in female patients.